Cannabis-Related Diffuse Alveolar Hemorrhage in a 16-Year-Old Patient: A Case Report - Bucchino, Laura; Monzani, Alice; Fracon, Sara; Genoni, Giulia; Cena, Tiziana; Bellone, Simonetta (Frontiers in Pediatrics, 2019)
Diffuse alveolar hemorrhage (DAH) is a clinical condition characterized by the rapid onset of dyspnea, hemoptysis and acute respiratory failure (ARF). It is commonly caused by autoimmune systemic vasculitis, pulmonary infections, drugs and tumors. Here, we report a case of DAH caused by frequent cannabis smoking. A 16-year old boy presented with hemoptysis, dyspnea and ARF soon after laparoscopic surgery for varicocele in general anesthesia. The suspected diagnosis of DAH emerged from the initial chest radiography, and it was then confirmed by CT scan findings and the bronchoalveolar lavage. His general conditions completely recovered after only 24 h of oxygen supplementation and after intravenous corticosteroid and antibiotic therapy. This is the first pediatric case of DAH related to smoking marijuana, even though the inhalational anesthetic agent sevoflurane might have also been involved in this pathogenesis. Other possible causes of DAH have been considered. Negative-pressure pulmonary edema could be ruled out because no clinical evidence of upper airway obstruction was observed during general anesthesia and throughout the surgery. In addition, a possible causative role of cannabis additives/contaminants could not be excluded. Given the high prevalence of cannabis smoking in young people and that DAH can be a complication in cannabis smokers, a careful history and high index of suspicion are recommended as part of the pre-operative assessment before these patients are proceeded to receive general anesthesia.